مدى توجيه الطلبة نحو ريادة الأعمال في منهاج التربية الإسلامية من وجهة نظر المعلمين - مصطفى، محمود أحمد (جامعة السلطان قابوس, 2022)
هدفت الدراسة إلى الكشف عن مدى توجيه الطلبة نحو ريادة الأعمال في منهاج التربية الإسلامية من وجهة نظر المعلمين. تكون مجتمع الدراسة من (530) معلما ومعلمة من معلمي المرحلة الثانوية في العاصمة عمان/ الأردن، وشملت العينة (210) من المعلمين والمعلمات في المدارس الثانوية اختيروا بطريقة عشوائية، منهم (106) معلما، و (104) معلمة، واتبعت الدراسة المنهجية الوصفية المسحية، ولتحقيق أهدافها أعدت استبانة تكونت من (35) فقرة. وأظهرت الدراسة أن توجيه منهاج التربية الإسلامية للطلبة نحو ريادة الأعمال جاء بدرجة متوسطة بشكل عام، وعدم وجود فروق دالة إحصائيا بين استجابات المعلمين تعزى إلى متغير الجنس أو الخبرة، وأوصت الدراسة بضرورة إعادة هيكلة المناهج لتكون داعمة للطلبة، وموجهة لهم نحو ريادة الأعمال. The study explores the extent to which students are directed towards entrepreneurship in the Islamic Education Curriculum from the teachers' perspectives. The researcher adapted the descriptive approach to achieve its main goal. The population consists of teachers at the secondary schools in Am-man, Jordan. The sample was randomly selected. There were (210) respondents. (106) males and (104) females. For gathering data, a survey questionnaire, with (35) items, was distributed. The current study revealed that directing the curricula for students towards entrepreneurship was intermediate in general. There are no gender-specific or experience-bound significant differences across the individuals’ responses towards the role of the curricula in students’ orientation towards entrepreneurship. The study recommends that there is a crucial need to restructure the curricula to be in support of students’ orientation towards entrepreneurship.
Keywords: إدارة الأعمال -- طلبة المدارس -- التعليم الثانوي -- المدارس الثانوية -- التربية الإسلامية